Study Living Hadith: Gus Asrofuddin's Ruqyah Treatment Practice in Setro Village, Sidoarjo - Ferdy Pratama; Amil Hikam Asaaf; Alwi Shobri; Sellyana Verawati; Ikmal Tahzibil Huda (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The practice of the Islamic religion in Indonesia which is often practiced by a group of Muslim people in particular has legality from a valid primary source of Islamic religious law. Although sometimes, the existing practices of the perpetrators do not know the source of this tradition, such as the practice of ruqyah treatment by Gus Ahmad Asrofuddin in Setro Village, Prambon District, Sidoarjo Regency which is believed to bring healing based on a hadith. By using a qualitative phenomenological approach, this research examines the extent to which the community’s healing rate and community’s response to Gus Asrofuddin ruqyah treatment, and hadith which form the basis of theory in the study of living hadith. On the other hand, the test uses interpretative phenomenological analysis theory as an approach to evaluatu activies based on interview results. The purpose of this study is to provide statistical data related to the issues raised. As a result, the people who seek treatment on average experience an increase in their recovery from the illness they suffer and the community does not feel that there is an element of shirk in the ruqyah treatment of Gus Asrofuddin.